Update on the distribution of Aedes albopictus (Diptera: Culicidae) in Misiones, Argentina - Leporace, Marina (2020)
Fil: Leporace, Marina. Instituto Universitario de Ciencias de la Salud. Fundación Barceló; Argentina.